Bioimpedance and bioelectricity basics - Martinsen, rjan Grttem; Heiskanen, Arto (Academic Press, 2023)
Bioimpedance and Bioelectricity Basics, Fourth Edition discusses, in detail, dielectric and electrochemical aspects, as well as electrical engineering concepts of network theory. The book takes readers from an introductory (postgraduate) level to a developed understanding of core dielectric and electrochemical aspects of bioelectricity combined with the necessary electrical engineering concepts, such as network theory, to allow readers to work effectively across the interface of biology, physics and engineering. The book has a highly effective organization, and covers important concepts relating to bioelectricity and impedance, including finite element analysis, endogenic sources, control theory, tissue electrical properties, and invasive measurements. With its concentration on instrumentation and system design, data and analysis, the book is suited to readers with an applied focus on experimentation and device development. It paves an easier and more efficient way for readers seeking basic knowledge about this discipline. This book's focus is on systems with galvanic contact with tissue, and the importance of the geometry of the measuring system cannot be overemphasized.